Imma phuocbuu Buchsbaum, Chi & Chen, sp. nov. from south Vietnam (Lepidoptera: Immidae) - Buchsbaum, Ulf; Chen, Mei-Yu; Minh Chi, Nguyen (SHILAP Revista de lepidopterología, 2024)
During a faunal survey of Lepidoptera in 2023, Imma phuocbuu Buchsbaum, Chi & Chen, sp. nov. was discovered and represents the first record of the genus in Vietnam. A single male specimen was collected from a transitional biotype between mangrove and semi-deciduous dry lowland forest habitats near the coast. The new species is distinguished from Imma transversella (Snellen, 1878), I. semicitra Meyrick, 1937 and I. semiclara Meyrick, 1929 by differences in wing pattern and genitalia morphology.